Volcanic stratigraphy and evidence of magma mixing in the Quaternary Payún Matrú volcano, andean backarc in western Argentina - Hernando, Irene Raquel (2012)
The Payún Matrú Volcanic Field is located in the Payenia Basaltic Province of the recent back-arc of western Argentina (35°S-38°S). This province is younger than 5 Ma, and most of its volcanic activity took place since 2 Ma. The Payún Matrú Volcanic Field contains two composite volcanoes, Payún Matrú and Payún Liso, and two basaltic fields in an E-W oriented zone, located east and west of the Payún Matrú volcano. Payún Matrú is the largest volcano of this volcanic field, and consists of a shield-shaped edifice with a circular summit caldera of 8 km in diameter. The composition of both composite volcanoes is alkaline and predominantly trachytic, having also minor intermediate lavas. The basaltic fields consist of basalts and trachybasalts, with clinopyroxene and abundant olivine as phenocrysts and also in the groundmass. Textures indicating mixing and mingling processes, such as dusty plagioclases along with clear ones, biotite replaced by anhydrous minerals and two groundmasses with a fluid-fluid relationship, are common in the early pre-caldera stage of Payún Matrú and some post-caldera lavas. The latest post-caldera lavas are trachytic, with clean sanidine phenocrysts without disequilibrium textures. A remarkable characteristic of the Payún Matrú Volcanic Field is the fact that the Payún Matrú caldera is surrounded by basaltic fields at its base, while no basalts were erupted in the caldera region. We propose that the absence of basaltic lavas in the Payún Matrú volcano is due to the presence of a magmatic chamber below it, and that the mafic magmas rising from deeper levels were unable to erupt without interaction with more evolved melts. Intermediate hybrid magmas produced as a consequence of magma mixing and mingling between basaltic and trachytic magmas, are present in the early and mid-history of Payún Matrú volcano. We present here new information about the Quaternary Payún Matrú Volcanic Field derived from field work, petrography, and major element geochemistry and 87 Sr/ 86 Sr isotopic ratios. For the first time a detailed map of the Payún Matrú Volcanic Field and its volcanic stratigraphy, primarily based on field observations, are presented.